Samodzielność wydatkowa samorządu terytorialnego - determinanty i mierniki oceny - Galiński, Paweł (Financial Independence of the Local Government in the Field of Expenditures - Determinants and Measures of Appraisal, 2009)
The aim of the paper is to determine the issues which affect the level of financial independence of the local government in the field of expenditures. The author indicates some financial and legal factors of that independence and its effects. There were also pointed out some threats of financial independence of local government in the field of expenditures. Moreover, there were shown some indicators which may appraise this independence and the solutions of increasing the effectiveness of public expenditures in the local government.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 50-58